A penhora on line e o direito à tutela jurisdicional efetiva - Parahyba, Andrea Joffily (2011)
Ineffectiveness of crisis by courts , especially with regard to executive tutelage , gave rise significant changes in the Brazilian civil procedural law, which redefined executives instruments already overcome the inefficiency and hindered to achieve an effective result. The overall objective of this thesis is to investigate how the online pledge institute relates to overcoming this crisis and therefore to the realization of the right to judicial protection . Therefore , we try to analyze the constitutional foundations of this procedural tool in the context of the principles of access to justice, the effectiveness of legal protection and proportionality.